Pengaruh faktor hidrologi terhadap pencemaran sampah padat di sungai (Studi kasus: Sungai Citarum, Jawa Barat) - Zainalarifin, Jauhar; Effendi, Hefni; Taryono, Taryono (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
River hydrological factors are thought to influence the level of solid waste pollution that occurs in the Ciliwung River, this is one of the problems that causes a decline in river water quality and threatens the health of the surrounding environment. This research aims to analyze the influence of hydrological factors on the condition of solid waste pollution in the river. The research was conducted in April-June and August-November 2021 at five monitoring locations spread across Bandung Regency, West Bandung Regency, Purwakarta Regency and Bekasi Regency. The analysis used is a linear regression with the river width (X1), water level (X2) and current speed (X3) on solid waste reporting (Y). The analytical equation model obtained from this is Y = 0.0394 – 0.0041 X1 with a coefficient of determination value of 9,33% with a correlation coefficient reaching 30.55%. This research proves that narrow river width can increase the distribution of solid waste. Although hydrological factors influence forest ecosystems, a stronger influence is thought to come from human behavior factors that throw rubbish directly into rivers.